Milrinone Pharmacokinetics and Pharmacodynamics in Neonates with Persistent Pulmonary Hypertension of the Newborn - Giaccone, Annie; Zuppa, Athena F.; Sood, Beena; Cohen, Meryl S.; O'Byrne, Michael L.; Moorthy, Ganesh; Mathur, Amit; Kirpalani, Haresh (American Journal of Perinatology, 2017)
Objective To describe the pharmacokinetics and pharmacodynamics of milrinone in infants with persistent pulmonary hypertension of the newborn (PPHN) and to explore the impact of age on milrinone disposition.Design Randomized, open label pilot study.Setting Multicenter; level 3 and level 4 neonatal intensive care units.Patients Six infants ≥34 weeks' gestational age and <10 days of life with persistent hypoxemia receiving inhaled nitric oxide.Intervention Intravenous milrinone lactate in one of two dosing regimens: (1) low dose, 20 mcg/kg bolus followed by 0.2 mcg/kg/minute, and (2) standard dose, 50 mcg/kg bolus followed by 0.5 mcg/kg/minute.Measurements and Main Results The final structural model was a two-compartment disposition model with interindividual variability estimated on clearance (CL). The estimated value of CL is 7.65 mL/minute/3.4 kg (3.05 mL/minute/kg). The addition of age improved the precision of the CL estimate, and CL increased with chronological age in days. The oxygenation index was highly variable within each participant and improved with time. There were no observed safety concerns in either dosing group.Conclusion The CL of milrinone in newborns with PPHN is reduced and increases with age. In this pilot study, we did not see significant pharmacodynamic or safety effects associated with drug exposure.
Keywords: persistent pulmonary hypertension of the newborn; meconium aspiration syndrome; milrinone; phosphodiesterase 3 inhibitors; vasodilator agents; pharmacokinetics